Developing Scientific Literacy-Based Teaching Materials to Improve Students’ Computational Thinking Skills - Fakhriyah, F.; Masfuah, S.; Mardapi, D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Computational thinking and scientific literacy are competencies compulsorily required by pre-service primary teachers in the 21st century. This study aimed to examine the effectiveness of scientific-based teaching materials that have been developed in improving the computational thinking skills of Primary School Education Department students of UniversitasMuria Kudus Indonesia. This research employed the Research & Development (R & D) procedure, which includes three stages, namely preliminary studies, development, and validation. In the validation stage, the scientific literacy-based materials were applied in large-scale trials with quasi-experimental control groups design for the fourth-semester students of Primary School Education Department in the academic year of 2018/2019, where class 4A as the control group and class 4C as the experimental group were taken randomly. The experimental class consisted of 44 students, while the control class consisted of 46 students. After being given the treatment, the two classes were given a post-test to examine its effectiveness. Based on the hypothesis testing using the right t-test, it has a tcountof 2,215 and ttableof 1.99. Thus, it could be concluded that the teaching materials of the developed scientific literacy concepts were effective in improving the students’ computational thinking skills.